Lead zinc slag-based geopolymer: Demonstration of heavy metal solidification mechanism from the new perspectives of electronegativity and ion potential. (15th January 2022) - Zhang, Qiushi; Cao, Xing; Sun, Shichang; Yang, Weichen; Fang, Lin; Ma, Rui; Lin, Chenghua; Li, Haowen
Abstract: Lead-zinc slag (LZS) is a solid waste product that is rich in silicon and aluminum and has enormous resource potential for functional environmental functional geopolymer materials. Unfortunately, the solidification mechanism of heavy metals in geopolymers is still unclear, which is detrimental to the heavy metal solidification of LZS. In this study, we comprehensively studied and demonstrated the solidification mechanisms of Pb and Zn in geopolymers, based on the preparation of high-performance LZS-based geopolymers (compressive strength up to 89.3 MPa, and Pb and Zn solidification efficiency up to 93.1% and 90.0%, respectively). Thereafter, the solidification mechanism differences between Pb and Zn were explained by electronegativity and ion potential. Due to the ionic potential order of Zn 2+ > Pb 2+ > Na +, both Zn 2+ and Pb 2+ could exchange with Na + in the geopolymer. In addition, due to the electronegativity order of Pb > Si > Zn, Pb could attack the [SiO4 ] structure and form covalent bonds in the Pb–O structure, while Zn did not (shown by Raman spectroscopy). As a result, Pb simultaneously solidified in the geopolymer through covalent bonding and ion exchange, while Zn was solidified mainly by ion exchange. Thus, this work provides new perspectives and ideas for the solidification mechanisms of heavy metals in geopolymers. Graphical abstract: Image 1 Highlights: Lead-zinc slag was used to prepare a geopolymer for recycling and mitigation. Various theories regarding the heavy metal solidification mechanism were identified. Ion exchange of Pb 2+ and Zn 2+ with Na + was explained by ionic potential. Difference between solidification behaviors of Pb and Zn due to the electronegativity.